The Enigma Performing Rights in Music Disputes in Indonesia: A Way of Justice from the Paradigm of Fairness Principle - Arini, Ida Ayu Vinda; Kurniawan, I Gede Agus (International Journal of Law Reconstruction, 2023)
This study aims to answer two legal issues, namely, the enigma and nature of the concept of performing rights in music disputes in Indonesia and the orientation of the principle of fairness in realizing justice related to music disputes in Indonesia related to performing rights. This research is a normative legal research with a concept and statutory approach. The research results confirm that performing rights in music disputes in Indonesia must be seen in the important role of LMKNs as regulators, administrators, as well as mediators. Therefore, increasing the professionalism and capacity of LMKNs is needed so that the distribution of royalties can reflect aspects of justice for those involved in the world of music. The fairness principle in realizing justice related to music disputes in Indonesia related to performing rights is when the original position and vail of ignorance of the parties are strengthened through the role of LMKN in the mediation process, namely that disputes related to performing rights can be carried out effectively, efficiently and refers to the substantive aspects which are proportionally able to accommodate the rights of the parties.